John Rawls and the recent history of public administration - Esquith, Stephen L (Journal of management history, 1997)
John Rawls' theory of justice has had a direct impact on public administration, especially work in new public administration. His theory has influenced the obligations of public administrators, the scope of citizen participation in public administration, and the equitable distribution of public services. It has also contributed to the development of administrative ethics. In addition, it suggests ways in which a mediating model of public reason might be developed for public administrators working on deeply divisive social and economic issues.